Crystallization and preliminary X‐ray diffraction studies of Drosophila melanogaster Gαo‐subunit of heterotrimeric G protein in complex with the RGS domain of CG5036. Issue 1 (8th January 2013) - Tishchenko, Svetlana; Gabdulkhakov, Azat; Tin, Uliana; Kostareva, Olga; Lin, Chen; Katanaev, Vladimir L.
<x xml:space="preserve">Abstract</x> Regulator of G‐protein signalling (RGS) proteins negatively regulate heterotrimeric G‐protein signalling through their conserved RGS domains. RGS domains act as GTPase‐activating proteins, accelerating the GTP hydrolysis rate of the activated form of Gα‐subunits. Although omnipresent in eukaryotes, RGS proteins have not been adequately analysed in non‐mammalian organisms. The Drosophila melanogaster Gαo‐subunit and the RGS domain of its interacting partner CG5036 have been overproduced and purified; the crystallization of the complex of the two proteins using PEG 4000 as a crystallizing agent and preliminary X‐ray crystallographic analysis are reported. Diffraction data were collected to 2.0 Å resolution using a synchrotron‐radiation source.